Roots and branches : a resource of Native American literature : themes, lessons, and bibliographies - Susag, Dorothea M.; National Council of Teachers of English (Urbana, IL : National Council of Teachers of English, 1998)
Presents study materials on Native American literature, addressing themes and historical and literary contexts, and including several bibliographies as well as information on non-Native authors' stories about Native Americans.
"NCTE stock number: 41951-3050"--T.p. verso.
Includes bibliographical references and index.
Multicultural Review.
Wilson's Junior High School.
Professional
Keywords: American literature -- Indian authors -- Bibliography; American literature -- Indian authors -- Study and teaching -- Outlines, syllabi, etc; American literature -- Indian authors -- Themes, motives, etc; Indian literature -- Bibliography; Indian literature -- Study and teaching -- Outlines, syllabi, etc; Indian literature -- Themes, motives, etc; Indians in literature -- Bibliography; American literature -- Native American authors; American literature -- Native American authors -- Bibliography; American literature -- Native American authors -- Study and teaching; Native American literature -- Bibliography; Native American literature -- Study and teaching; Native Americans in literature -- Bibliography